JUAL BELI BIBIT TANAMAN DENGAN SISTEM ONLINE - R. Fakhrurrazi; Siti Hanifa (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2024)
The development of technology has facilitated various activities, including buying and selling. With technological advancements, individuals no longer need to struggle to obtain the desired goods. One thing that makes it easier is the online buying and selling system. This includes the online sale of plant seeds, which is currently very common. The online sale of plant seeds poses many risks, such as damage and others. This research aims to reveal the mechanisms of online plant seed trading and explore the perspective of Islamic law on the mechanisms of online plant seed trading. The research data was gathered through documentation available on online plant seed trading facilities. The research results conclude that the relationship between the two parties in the salam contract agreement with the online system is the same as in traditional salam contract agreements. However, in an online salam contract, the buyer and seller do not meet face to face; they are only connected through an internet site. In practice, the seller posts various types of plant seeds on Facebook or WhatsApp, along with the seller's phone number to facilitate transactions for consumers. However, sellers face difficulties in adjusting the size of the ordered seeds in large quantities because each seed has a different size. Therefore, the seller only matches the similarity without re-measuring. From the perspective of Islamic law, the mechanism of online plant seed trading can be concluded as permissible, as long as it does not contain elements that can damage it, such as usury (riba), fraud, cheating, injustice, and others, and it must fulfill the pillars and conditions in conducting buying and selling transactions.